Pembelajaran Ansambel Musik Pada Kegiatan Ekstrakurikuler di SMA Negeri 1 Tanjung Lago - Yosi Manda Pratama; Fadhilah Hidayatullah; Muhsin Ilhaq (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Extracurricular music learning for school children, especially at high school level, aims to develop their creativity and talents. This activity includes comprehensive planning, implementation and evaluation, not only to hone musical skills but also to stimulate their creative potential.